The Development of Puzzle Games for Early Childhood Based on the Banten Local Culture - Asmawati, Luluk (SCAD Independent, 2023)
Developing a digital puzzle game model is a learning innovation for early childhood cognitive development. The current research purpose was to develop a digital games puzzle based on Banten culture for early childhood; The method applied was the research and development of ADDIE's model with the 30 children as samples. The results revealed five puzzle game objects and levels 1-3. The weakness of this puzzle game was that there was no animation, while the advantages of this puzzle game were that it was easy to be used by children; it could be used via Android and laptops, the game menus were easy to understand, it has attractive design and game background, and it was provided with game tutorials. The material expert test results were 88%, which was very feasible; the media expert test results were 85%, which was also very feasible; and the field test results were 97%, excellent. This research concluded that the data processing using paired t-tests obtained a sig value of 0.000, less than 0.05 (0.000 <0.05). Then it could be obtained the decision to reject Ho. It means that there were differences in children learning outcomes before and after using puzzle games.